Media Pembelajaran Proses Rendering Objek 3D Berbasis Multimedia - Supriyadi Sandi (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
3D Animation Learning on object rendering material for some students is very difficult to understand. The number of students who need aids in the form of learning media more than the number of students who do not need. For that need to be built 3D animation learning applications, especially on the object rendering material for students to use as a means of learning and facilitate lecturers in delivering the material.Subject in this research is 3DMax multimedia application as 3D learning media of Animation on object rendering. Data collection in this research using literature study method, observation method, and interview method. Applications are prepared by procedures that include identifying the problems obtained, needs analysis, designing concepts, designing contents, design documents and navigation diagrams, designing scripts, designing graphics, producing systems, testing systems with black boxes and alpha test.The result of this research is multimedia application as learning media of 3D animation on object rendering material for student of Broadcast Study Program at AKOM BSI Jakarta which based on result of testing it can be concluded that this learning application can help the learning process in students to understand the material and can be used as a tool lecturer to support 3D animation learning.